The Representation Of Javanese Women In Damar Kurung Painting – Gresik - Aniendya Christianna (Mudra Jurnal Seni Budaya, 2018)
Damar Kurung is one of the typical cultural products of Gresik that has recorded Gresik’s civilization. Damar Kurung is a bamboo-framed paper lantern that has existed since Hindu-Buddhist times. This research is a qualitative research with a descriptive approach. The purpose of this research is to understand the meaning of the symbol in Damar Kurung’s decorative that are painted by Masmundari. At the same time to identify the gender roles of Javanese women. The results of this study are (1) Javanese women do not reject face makeup, because using makeup is a manifestation of women’s respect and acceptance in dealing with social norms; (2) Javanese women formulate their identity through a procession of traditional ceremonial preparations that are mostly carried out ‘behind’ (in the kitchen).Damar Kurung merupakan salah satu produk budaya khas Gresik yang telah merekam peradaban masyarakat Gresik. Damar Kurung adalah lampion kertas berangka bambu ini sudah ada sejak zaman Hindu-Budha. Penelitian ini adalah penelitian kualitatif dengan pendekatan deskriptif. Tujuan dari penelitian ini untuk memahami makna simbol di damar kurung yang dilukis oleh Masmundari. Sekaligus untuk mengidentifikasi peran gender perempuan Jawa. Hasil dari penelitian ini adalah (1) perempuan Jawa tidak menolak riasan wajah, karena menggunakan riasan adalah perwujudan penghormatan dan penerimaan perempuan dalam menghadapi norma sosial;(2) perempuan Jawa merumuskan identitasnya melalui prosesi persiapan upacara adat yang banyak dilakukan ‘dibelakang’ (di dapur).